Risk factors for perimenopausal depression in Chinese women: a meta-analysis - Gan, Qingwen; Yu, Ran; Lian, Zerong; Wei, Lihua; Li, Yuanping; Yuan, Yiling; Zheng, Lilan (Frontiers in Psychiatry, 2023)
Objective To systematically evaluate the risk factors for perimenopausal depression in Chinese women and to provide a basis for screening perimenopausal women at high-risk for depression. Methods A computer search of seven databases, including SinoMed, PubMed, Web of Science, and so on, and two clinical trial registries on the risk factors for depression in Chinese women during perimenopause was conducted for meta-analysis. The search time limit was from the establishment of the database to December 2022. The included case–control and cross-sectional studies were evaluated using the Newcastle–Ottawa scale (NOS) and criteria developed by the Agency for Healthcare Research and Quality (AHRQ). Results A total of 15 papers with 12,168 patients and 18 risk factors were included. Meta-analysis results showed that the risk factors for depression in perimenopausal women were relationship quality [OR = 1.23, 95% confidence intervals (1.03, 1.46)], marital status [OR = 2.49, 95% CI (1.77, 3.50)], family income [OR = 1.48 95% CI (1.10, 2.00)], comorbid chronic diseases [OR = 2.39, 95% CI (1.93, 2.95)], exercise status [OR = 1.63, 95% CI (1.26, 2.11)], perimenopausal syndrome [OR = 2.36, 95% CI (2.11, 2.63)], age [OR = 1.04, 95% CI (1.01, 1.07)], and stressful events [OR = 12.14, 95% CI (6.48, 22.72)], and social support was a protective factor [OR = 0.76, 95% CI (0.63, 0.91), p < 0.05]. Conclusion Based on the exploration of risk factors for perimenopausal depression in Chinese women, we aimed to provide guidance for the screening of risk factors for depression in perimenopausal women and thereby reduce the incidence of depression. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/#myprospero, CRD42023403972.